Endoscopical and pathological dissociation in severe colitis induced by immune-checkpoint inhibitors. (1st January 2020) - de Andrea, Carlos Eduardo; Perez-Gracia, Jose Luis; Castanon, Eduardo; Ponz-Sarvise, Mariano; Echeveste, Jose I.; Melero, Ignacio; Sanmamed, Miguel F.; Rodriguez-Ruiz, Maria Esperanza
ABSTRACT: Checkpoint inhibitors have improved the survival of patients with advanced tumors and show a manageable toxicity profile. However, auto-immune colitis remains a relevant side effect, and combinations of anti-PD1/PDL1 and anti-CTLA-4 increase its incidence and severity. Here, we report the case of a 50-year-old patient diagnosed with stage IV cervical cancer that relapsed following radical surgery, external radiation/brachytherapy and standard chemotherapy. She was subsequently treated with Nivolumab and Ipilimumab combination and developed grade 2 colitis presenting a dissociation between endoscopic and pathological findings. At cycle 10 the patient reported grade 3 diarrhea and abdominal discomfort, without blood or mucus in the stools. Immunotherapy was withheld and a colonoscopy was performed, showing normal mucosa in the entire colon. Puzzlingly, histologic evaluation of randomly sampled mucosal biopsy of the distal colon showed an intense intraepithelial lymphocyte infiltration with crypt loss and some regenerating crypts with a few apoptotic bodies set in a chronically inflamed lamina propria, consistent with the microscopic diagnosis of colitis. Treatment with methylprednisolone 2 mg/﻿kg was initiated which led to a decrease in the number of stools to grade 1. Additional investigations to exclude other causes of diarrhea rendered negative results. The patient experienced a major partial response and, following the resolution of diarrhea, she was re-challenged again with immunotherapy, with the reappearance of grade 2 diarrhea, leading to permanent immunotherapy interruption. We conclude and propose that performing random colonic biopsies should be considered in cases of immune checkpoint-associated unexplained diarrhea, even when colonoscopy shows macroscopically normal colonic mucosa inflammatory lesions.